Предмет:
МатематикаАвтор:
анонимРаскроем скобки, для этого используем формулу квадрата разности и разности квадратов:
1) (2а - 3)^2 = (2а)^2 - 2 * 2а * 3 + 3^2 = 4а^2 - 12а + 9;
2) (а^4 - 4а)^2 = (а^4)^2 - 2 * а^4 * 4а + (4а)^2 = а^8 - 8а^5 + 16а^2;
3) (2 - 7а) * (2 + 7а) = 2^2 - (7а)^2 = 4 - 49а^2;
4) (а^3 + 4) * (4 - а^3) = (4 + а^3) * (4 - а^3) = 4^2 - (а^3)^2 = 16 - а^6;
5) Упростим выражение:
(х + 7) * (7 - х) - (х - 7)^2 = (7 + х) * (7 - х) - (х - 7)^2 = 7^2 - х^2 - (х^2 - 2 * х * 7 + 7^2) = 49 - х^2 - х^2 + 14х - 49 = 14х - 2х^2 = 2х * (7 - х).
Автор:
nicolás26Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть